Serological and molecular detection of parvovirus b19 in children with acute lymphoblastic leukemia. - Iqbal M. Abdullah; Shatha F. Abdullah; Mazin F. Al-Jadiry (مجلة كلية الطب, 2014)
Background: Human parvovirus B19 (B19V) is the only human pathogenic parvovirus, It is highly erythrotropic and preferentially replicates in erythroid progenitor cells (EPCs). Recently the effects of B19 infection have been well studied in children with acute lymphoblastic leukemia (ALL).